2011
DOI: 10.3354/ame01497
|View full text |Cite
|
Sign up to set email alerts
|

Influence of altered light conditions and grazers on Scrippsiella trochoidea (Dinophyceae) cyst ­formation

Abstract: We investigated whether or not the presence of copepods and different light conditions induced cyst formation in dinoflagellates. Scrippsiella trochoidea was exposed to Acartia tonsa directly and indirectly (grazer filtrate), in high light and low light conditions. The ingestion, faecal production and egg production of A. tonsa were compared between diets of S. trochoidea vegetative cells and temporary cysts. We found no effect of direct or indirect exposure to A. tonsa on S. trochoidea cyst formation in eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…The mixotrophic capacity of species of Scrippsiella and Woloszynskia to feed on small eukaryote cells (Jeong et al ., ; Kang et al ., ) may explain the strong persistence of these pigmented dinoflagellates at low light. The relatively lower proportion of Scrippsiella reads detected by cDNA in the low light, compared with high light, was consistent with reports of encystment at low irradiances (Rintala et al ., ; Lundgren & Granéli, ). In contrast, Woloszynskia reads were significantly (Metastats P ‐value < 0.05) more represented in the low light bottles.…”
Section: Discussionmentioning
confidence: 97%
“…The mixotrophic capacity of species of Scrippsiella and Woloszynskia to feed on small eukaryote cells (Jeong et al ., ; Kang et al ., ) may explain the strong persistence of these pigmented dinoflagellates at low light. The relatively lower proportion of Scrippsiella reads detected by cDNA in the low light, compared with high light, was consistent with reports of encystment at low irradiances (Rintala et al ., ; Lundgren & Granéli, ). In contrast, Woloszynskia reads were significantly (Metastats P ‐value < 0.05) more represented in the low light bottles.…”
Section: Discussionmentioning
confidence: 97%
“…For pellicle cysts, similar investigations into the effect of anoxia are for the most part lacking. The formation of pellicle cysts as a strategy to cope with darkness has been reported for species of the genus Scrippsiella [ 86 ], in which respiratory rates in the dark were reduced to very low levels [ 86 , 87 ].…”
Section: Functions Of Dinoflagellate Cystsmentioning
confidence: 99%
“…The same study also suggested that dinoflagellate cysts are able to detect chemical signals emitted by predators. However, in another report, there was no apparent influence of the copepod Acartia tonsa on the formation of pellicle cysts by Scrippsiella trochoidea [ 86 ]. In this dinoflagellate species, allelopathic effects on pellicle cyst formation may provide a defensive response to deleterious chemical cues [ 88 ].…”
Section: Functions Of Dinoflagellate Cystsmentioning
confidence: 99%
“…Resting cysts in sediments can resist harsh environmental conditions and are protected from viruses, grazers and parasite attacks (Ribeiro et al, 2011 ; Bravo and Figueroa, 2014 ). Encystment is usually considered to be an adaptive response to environmental stresses, such as nutrient depletion (Anderson et al, 1984 ; Grigorszky et al, 2006 ), changes in temperature (Sgrosso et al, 2001 ; Grigorszky et al, 2006 ), salinity (Zonneveld and Susek, 2007 ), day length (Sgrosso et al, 2001 ), high cell densities (Garcés et al, 2004 ) and bacterial attack (Lundgren and Granéli, 2011 ). However, little has been understood about the endogenous regulatory factors and physiological mechanisms for resting cyst fosrmation and germination (i.e., encystment and excystment) (Tang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%